Experimental methods of portal hypertension studying - D. V. Garbuzenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
The aim of review. To present methods of studying of portal hypertension and means of its pharmacological treatment in experiment settings.Original positions. To study complex pathophysiological disorders, innate to portal hypertension, various pilot models providing complex evaluation and development of adequate treatment methods are used. Nowadays mechanisms of hyperdynamic circulatory status development are detailed on laboratory animals. Ex vivo studies gave physiological characteristic to the mediators causing splanchnic vasodilation and increasing of vascular tension in cirrhotic liver, and methods of molecular biology identified defects in signalling routes responsible for disorders of metabolism of these substances.Conclusion. In the last years application of various pilot models of portal hypertension promoted progress not only in understanding of pathophysiological mechanisms laying in its basis, but also development of new perspective methods of treatment. The further randomized controlled clinical studies will help to determine their safety and efficacy comparing to traditional treatment methods.